Pengaruh kesadaran wajib pajak dan sanksi perpajakan terhadap kepatuhan wajib pajak kendaraan bernotor di samsat kota ternate dan kota tidore kepulaun - Sitti Nurkhalisa Habib (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
In the city of Ternate and the City of Tidore Islands, every year the number of taxpayers registered with SAMSAT continues to increase. However, with the increasing number of motor vehicle taxpayers, the number of taxpayers who pay taxes is not compensated for. The number of taxpayers who are in arrears in paying motor vehicle taxes in the City of Ternate and the City of Tidore Islands shows that the level of taxpayer compliance is still low in paying their taxes. This study aims to determine the effect of taxpayer awareness and tax sanctions on motor vehicle taxpayer compliance in the city of Ternate and the city of Tidore Islands. This type of research is quantitative, with the method of collecting data through questionnaires. Based on the Slovin formula, a sample of 100 taxpayers was obtained. The data analysis technique used in this research is multiple linear regression analysis. The results in this study state that taxpayer awareness has an effect on compliance with motorized vehicle taxpayers in the city of Ternate, but the results are different from what was done in the city of Tidore which said that taxpayer awareness had no effect on motor vehicle taxpayer compliance. motor vehicle tax compliance in the city of Ternate and in the city of Tidore.. Keywords : taxpayer awareness, taxation sanctions, taxpayer compliance.